Long-lasting immune responses 4 years after GAD-alum treatment in children with type 1 diabetes. - Stina Axelsson (Public Library of Science (PLoS), 2011)
A phase II clinical trial with glutamic acid decarboxylase (GAD) 65 formulated with aluminium hydroxide (GAD-alum) has shown efficacy in preserving residual insulin secretion in children and adolescents with recent-onset type 1 diabetes (T1D). We have performed a 4-year follow-up study of 59 of the original 70 patients to investigate long-term cellular and humoral immune responses after GAD-alum-treatment. Peripheral blood mononuclear cells (PBMC) were stimulated in vitro with GAD(65). Frequencies of naïve, central and effector memory CD4+ and CD8+ T cells were measured, together with cytokine secretion, proliferation, gene expression and serum GAD(65) autoantibody (GADA) levels. We here show that GAD-alum-treated patients display increased memory T-cell frequencies and prompt T-cell activation upon in vitro stimulation with GAD(65), but not with control antigens, compared with placebo subjects. GAD(65)-induced T-cell activation was accompanied by secretion of T helper (Th) 1, Th2 and T regulatory cytokines and by induction of T-cell inhibitory pathways. Moreover, post-treatment serum GADA titres remained persistently increased in the GAD-alum arm, but did not inhibit GAD(65) enzymatic activity. In conclusion, memory T- and B-cell responses persist 4 years after GAD-alum-treatment. In parallel to a GAD(65)-induced T-cell activation, our results show induction of T-cell inhibitory pathways important for regulating the GAD(65) immunity.